A study on factors that affecting the volatility of crude palm oil prices in Malaysia / Nurhanisa Mustafa - Mustafa, Nurhanisa (2011)
This paper provides a study on factors that affecting the volatility of crude palm oil prices in Malaysia. In this research, a multiple linear regression model is used to determine the relationship between crude petroleum oil prices, soybean oil prices, production of palm oil and crude palm oil prices. The econometric model is tested by using Statistical Procedure of Social System in order to identify the correlation and significant of the variables. The data used for this study is from January 1999 until December 2009 time period in monthly basis. The result then discussed in relation to the current and expected fundamentals of the palm oil market. As a conclusion, the study found that there is significant relationship between crude petroleum oil prices and soybean oil prices with crude palm oil prices in Malaysia. However, the production of crude palm oil have insignificant influence on Malaysian crude palm oil prices